Determination of dissolution conditions of galena concentrate in nitric acid solution with hydrogen peroxide - Aras, Ali; Ucar, Gokhan; Boyrazli, Mustafa; Aydogan, Salih (My University, 2007)
The leaching conditions of galena (PbS) concentrate in nitric acid (HNO3) medium containing hydrogen peroxide (H2O2) were investigated in this study. Effects of stirring speed in the range of 0 to 600 rpm, nitric acid concentration in the range of 0.1 to 2.0 M, hydrogen peroxide concentration in the range of 0.25 to 2.0 M, leaching temperature in the range of 23 to 60°C, particle size range of -212 +106, -106 +75, -75 +45 ?m on lead dissolution were investigated. According to obtained results, it was determined that the lead dissolution from galena in nitric acid medium with hydrogen peroxide was directly proportional by nitric acid and hydrogen peroxide concentrations and leaching temperature. It was increased with decreasing particle size. In addition to the lead dissolution from galena was independent by stirring speed. The lead dissolution of 100% was obtained by in following conditions: leaching time of 90 minutes, stirring speed of 200 rpm, nitric acid concentration of 0.75 M, hydrogen peroxide concentration of 1.0 M, leaching temperature of 50 °C, particle size of -75 +45 ?m and solid/liquid ratio of 1/500 g/ml.
7th International Scientific Conference on Modern Management of Mine Producing, Geology and Environmental Protection, SGEM 2007 -- 11 June 2007 through 15 June 2007 -- Albena -- 101475
Keywords: Dissolution; Galena; Hydrogen peroxide; Nitric acid